2015
DOI: 10.1080/19371918.2014.969858
|View full text |Cite
|
Sign up to set email alerts
|

Family Caregiver's Perception of Alzheimer's Disease and Caregiving in Chinese Culture

Abstract: This study examined the perception of Alzheimer's disease (AD) and caregiving among family caregivers of individuals with mild cognitive impairment (MCI) and AD in China. In-depth semistructured interviews were conducted with 46 family caregivers of individuals with cognitive impairment in 2009 in Wuhan and Beijing, China. Participants included 38 spouses, 7 adult children, and 1 sibling, aged between 41 and 85 years old. The findings showed that all family caregivers thought the Chinese terminology of AD laon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
44
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 40 publications
1
44
1
Order By: Relevance
“…Perceiving that caring for PWD is morally justified, and religiously and spiritually fulfilling, aligns with the Iranian tradition and Islamic belief [2]. It encourages family support, respect for the elders, and altruistic respect for patients, which is ultimately self-satisfying [33, 34]. Religiosity has been linked to having an agreeable and conscientious attribute [35].…”
Section: Discussionmentioning
confidence: 99%
“…Perceiving that caring for PWD is morally justified, and religiously and spiritually fulfilling, aligns with the Iranian tradition and Islamic belief [2]. It encourages family support, respect for the elders, and altruistic respect for patients, which is ultimately self-satisfying [33, 34]. Religiosity has been linked to having an agreeable and conscientious attribute [35].…”
Section: Discussionmentioning
confidence: 99%
“…This could be partly due to their misunderstanding of the nature of dementia. More than half of the respondents believed that “dementia is part of normal aging.” This belief was shared by Latino and African-American older adults as well as dementia caregivers in China (15, 25–30). In addition, biomarkers for early diagnosis of dementia are yet to be validated (31).…”
Section: Discussionmentioning
confidence: 99%
“…Many Chinese older adults prefer to be taken care of by their families. 5 Dementia caregiving in Chinese culture is considered a family affair and family members are expected to take full responsibility for providing care for their aging parents. 6,7 Chinese caregivers have consistently reported burden and stress when caring for family members with dementia.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Chinese caregivers have consistently reported burden and stress when caring for family members with dementia. 5,8,9 Research has found that chronic exposure to high burdens of care leads to detrimental physical and mental health consequences, such as increased depressive and anxiety symptoms, as well as increased risks for cardiovascular disease and hypertension. 10,11 Early-stage dementia is seen by Chinese people as normal aging, but the behavioral disturbances and neuropsychiatric symptoms of late-stage dementia are stigmatized.…”
Section: Introductionmentioning
confidence: 99%